(untitled) (Gragoatá, 2023)
Resenha de: PHAN, Le Ha. Transnational Education Crossing ‘Asia’ and ‘the West’. Adjusted desire, transformative mediocrity and neo-colonial disguise. New York: Routledge, 2018. 260 p.